Similarities and Differences in the Acute-Phase Response to SARS-CoV-2 in Rhesus Macaques and African Green Monkeys - Coleman, Celeste; Doyle-Meyers, Lara A.; Russell-Lodrigue, Kasi E.; Golden, Nadia; Threeton, Breanna; Song, Kejing; Pierre, Genevieve; Baribault, Carl; Bohm, Rudolf P.; Maness, Nicholas J.; Kolls, Jay K.; Rappaport, Jay; et al. (Frontiers in Immunology, 2021)
Understanding SARS-CoV-2 immune pathology is critical for the development of effective vaccines and treatments. Here, we employed unbiased serial whole-blood transcriptome profiling by weighted gene network correlation analysis (WGCNA) at pre-specified timepoints of infection to understand SARS-CoV-2-related immune alterations in a cohort of rhesus macaques (RMs) and African green monkeys (AGMs) presenting with varying degrees of pulmonary pathology. We found that the bulk of transcriptional changes occurred at day 3 post-infection and normalized to pre-infection levels by 3 weeks. There was evidence of coordination of transcriptional networks in blood (defined by WGCNA) and the nasopharyngeal SARS-CoV-2 burden as well as the absolute monocyte count. Pathway analysis of gene modules revealed prominent regulation of type I and type II interferon stimulated genes (ISGs) in both RMs and AGMs, with the latter species exhibiting a greater breadth of ISG upregulation. Notably, pathways relating to neutrophil degranulation were enriched in blood of SARS-CoV-2 infected AGMs, but not RMs. Our results elude to hallmark similarities as well as differences in the RM and AGM acute response to SARS-CoV-2 infection, and may help guide the selection of particular NHP species in modeling aspects of COVID-19 disease outcome.